Frequency of proteinuria in type 2 diabetes mellitus seen at a diabetes centre in southern India. Issue 899 (1st September 2000) - Mohan, V; Meera, R; Premalatha, G; Deepa, R; Miranda, P; Rema, M
Abstract : The frequency of proteinuria was assessed in a cohort of 1848 diabetic patients attending a diabetes centre in south India. A total of 127 (6.9%) patients had evidence of macroproteinuria and 49 (2.5%) patients had microproteinuria. Thus overall 9.4% of patients had diabetes related proteinuria. In addition, 70 patients (3.8%) had evidence of proteinuria with no evidence of retinopathy. The frequency of both microproteinuria and macroproteinuria increased linearly with duration of diabetes. Multiple logistic regression analysis showed that duration of diabetes, serum creatinine, and glycated haemoglobin were risk factors for macroproteinuria.